Pilgrims of Love: The Anthropology of a Global Sufi Cult by Pnina Werbner (London: Hurst & Co., 2003. 348 pages.) (American Journal of Islam and Society, 2006)
Pnina Werbner’s Pilgrims of Love, a truly exceptional book in several importantways, is the result of some eleven years of fieldwork in Britain andPakistan. While the topic, understanding a transnational Sufi cult, is quiteconventional within the discipline of anthropology, the time span in which theresearch was conceived and conducted is perhaps one wherein anthropology began to question seriously even its most taken-for-granted truths. Thismakes the final product anything but conventional.The author makes very clear her position as an anthropologist and thedifficulties she experienced as a western Jewish female academic writingabout a Pakistani, or second-generation Pakistani, predominantly Muslimmale practitioner’s perspective. Her honesty about the nature of her fieldexperience, the classic nature of the research itself within the canon ofanthropological literature, and her assessment of what she calls “the limitsof postmodern anthropology” (pp. 14-15, 291-302) add a certain depth ofsubstance to the discipline’s ongoing discussion of the subject-object relationship.This text is an important contribution to the body of literaturewithin the anthropology of religion and Islam, comparative studies of Islamicmovements, transnationalism, and, in general, to students and scholars ofPakistan and South Asia ...